Continuous flow nitration of salicylic acid - Kulkarni, Amol A.; Nivangune, Nayana T.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2008)
Continuous flow nitration of salicylic acid using HNO3/AcOH was studied in the SS316 tubular microreactor. At specific reaction conditions, complete conversion of the reactant was achieved in less than 7 min. It yielded only mononitro derivatives with a higher selectivity of 5-nitrosalicylic acid. Presence of the lower amount of acetic acid in the reaction mixture was seen to be detrimental, leading to precipitation of the desired product (5-nitrosalicylic acid). Reaction at higher temperatures yielded byproducts. The continuous mode operation using the system comprising the microdevices was demonstrated for 2 h with consistent composition at the outlet.